Sacroplasty with or without screw fixation for sacral metastatic tumors - Cox, Evan P.; Tutton, Sean; Scheidt, Matthew; Key, Brandon M.; Neilson, John C.; Wooldridge, Adam N.; Bedi, Meena; Hackbarth, Donald A.; King, David M. (Frontiers in Oncology, 2025)
IntroductionCementation (sacroplasty) with or without ablation has been shown to improve pain and function for patients with sacral metastatic disease. Percutaneous screw fixation with sacroplasty (PSFS) may provide superior outcomes in select patients.MethodsThirty patients with sacral metastases who underwent sacroplasty with or without ablation and screw fixation at a single institution were retrospectively reviewed. Patients were compared based on treatment (PSFS or sacroplasty alone) and fracture status (pathological or impending) with an ANCOVA. Traumatic fractures were excluded. Patients were followed for 4.4 months on average (range, 2 weeks to 36.5 months). Functional outcomes were assessed using the Musculoskeletal Tumor Society (MSTS) score. The rate of secondary procedures as well as changes in narcotic usage were noted.ResultsPatients with pathological fractures who underwent PSFS demonstrated increased postoperative MSTS scores compared to those who underwent sacroplasty (51% ± 19 versus 25% ± 13, p = 0.005). Patients with impending pathological fractures who underwent PSFS did not demonstrate statistically significant increased postoperative MSTS scores compared to those who underwent sacroplasty alone (38% ± 17 versus 32% ± 12, p = 0.72).DiscussionPSFS may provide additional benefit for patients with pathological fractures, while sacroplasty alone may be sufficient for those with impending pathologic fractures secondary to sacral metastatic disease. This study was limited by its retrospective design and sample size; however, the results may aid in treatment indications for sacral metastases and guide further research Level of Evidence Level III, Therapeutic Study.